Redefining mosque ornamentation in Malaysia, cross comparative analysis on post-modern perspective : (a case study of Charles Jencks and Michael Graves). - Utaberta, Nangkula; Handryant, Aisyah Nur; Nik Ab. Wahab, Nik Syazwan (2014)
Ornamentation is the key element that is used in most mosques all over the world. Ornamentation in general are known and used since pre-historic era. People at that time; decorate their religious monument such as temple with some symbol of their belief. Many ornamentation motifs in Egyptian are symbolic of their belief, like sun and sacred beetle as symbol of God. The development of ornamentation then continue in Greek, Rome, Gothic, even in Modern era, -the era which many people thought that there no ornamentation- Baroque, and Post-Modern era. The ornamentation product of each eras is always has different background and purpose. Ornamentation in Islamic building has recorded in many books. Creswell (1958) describe that one of the first ornamentation in Islamic Building found in Persia which is using revivalism approach in designing ornament in its column. While Jencks (1977) told that building including his ornamentation should have a meaning in order not to wrongly interpret by general people. Further, he told that to communicate meaning to community, architect should have some methods which referring architecture as a language. Then, according Michael Graves's approach, who told that even he used elements of previous architectural buildings but he only use the essence derived from the visual message without imitating the elements. With this principle, the ornamentation has different appearance and different meaning in it. Nowadays, the ornamentation in many mosques found has imitation issue. The ornamentation just follow same form previous ones without have essential meaning. All of these ornamentations in mosque which use direct historical precedence is in line with Jencks's criticism on classical modernism. The aim of this writing is to provide the Charles Jencks & Michael Grave's approaches to evaluating ornamentation system in mosque especially in Malaysia.